Factors Impacting Satisfaction and Loyalty Towards Network Teaching Platform Among Students Majoring in Humanities and Social Sciences in Chengdu, China - Xiao, Donghua (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
This research aims to evaluate influencing factors of satisfaction and loyalty towards network teaching platform among students majoring in humanities and social sciences in Chengdu, China. The conceptual framework was built based on trust, experience, service quality, perceived value, privacy, satisfaction, and loyalty. Quantitative method was applied for this research by using probability and nonprobability methods, The sampling techniques are judgmental, stratified random and convenience sampling. 517 samples were collected from two target universities, namely Xihua University (XHU) and Jincheng College of Chengdu (JCCCD). Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM) were utilized to determine the relationships of the variables. The results show that service quality, perceived value, privacy and trust have a significant impact on satisfaction. Additionally, satisfaction and trust significantly impact loyalty. Conversely, experience has no significant impact on satisfaction. online teaching platform developers, educators, and universities must continuously improve service quality, make users perceive the platform’s value, protect users’ privacy, and make them believe the platforms are trustworthy.